Sosialisasi dan Implementasi Program Lesson Study for Learning Community di Perguruan Mathla’ul Anwar se-Banten - Veny Agustini Prianggita; Purlilaiceu Purlilaiceu; Ade Hidayat; Erna Irawati; Risma Sutihat; Itoh Masitoh; Amelia Ayu Pratiwi (Universitas Mathla'ul Anwar Banten, 2020)
THE SOCIALIZATION AND IMPLEMENTATION OF THE LESSON STUDY FOR LEARNING COMMUNITY PROGRAM AT MATHLA'UL ANWAR COLLEGE IN BANTEN. Lesson Study is a model of fostering the teaching profession through mastering collaborative and sustainable learning based on the principles of collegiality and mutual learning to improve the quality of learning and build learning communities. Dissemination of Lesson Study in Mathla'ul Anwar Banten is considered to be very potential to be able to encourage many parties to do their best to improve the quality of learning and be able to increase achievement motivation in students. One of the goals expected by Lesson Study is to develop a pattern of educating teacher competencies with the LSLC model. The benefits of this Dissemination activity will be the establishment of a training system that is needs-based and sustainable in order to improve the quality of learning. The results of LSLC dissemination have become a model for educating teachers to improve teacher competence and improve the quality of learning in the classroom.